Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Kebijakan Hutang, dan Likuiditas Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur - Mas Intan Purba; Juliana Lorent; Aditya Angga; Cynthia Cynthia; Juli Juli (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
PAbstract - The purpose of this study is to examine and analyze the effect of Profitability, Company Growth, Debt Policy, and Liquidity towards Dividend Policy on manufacturing companies listed on the IDX in 2014-2017, both partially and simultaneously. This study's method is quantitative descriptive study.  These population are manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017, amounting to 156 companies. The sample in this study are 43 companies selected with certain criteria.  The statistical method used was multiple linear regression analysis.  The results showed that profitability, company growth and debt policy significantly influence the dividend policy. Whereas Liquidity has no effect and insignificant on Dividend Policy.  And simultaneously Profitability, Company Growth, Debt Policy, and Liquidity have a significant effect on Dividend Policy. The magnitude of the determination coefficient of 0.161 means that only 16.1% of the Dividend Policy can be explained Profitability, Company Growth, Debt Policy, and Liquidity, while the remaining 83.9% was explained by other variables not examined in this study such as company size and ownership structure. The conclusion of this study is that partially only Profitability, Company Growth and Debt Policy, significantly influence towards Dividend Policy on manufacturing companies listed on the IDX in 2014-2017. Keywords: Company Growth, Debt Policy, and Liquidity towards Dividend Policy